Itanong mo kay daddy o! questions the "young" would frequently ask - Cabrillas, Obet (Shepherd's Voice Publications, Inc., 2014)
This book contains questions from real people who are searching for life's meaning and purpose. Daddy O answers and shares precious wisdom coming from his own experience of God's grace and the lessons he learned in the university of life. These questions may be your questions, too. Their enlightenment, healing and freedom can also be yours.